2016
DOI: 10.1016/j.carbon.2016.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive measurement of photoexcited carrier transport in graphene with ultrafast grating imaging technique

Abstract: Graphene has great potential for fabrication of ultrafast opto-electronics, in which relaxation and transport of photoexcited carriers determine device performance. Even though ultrafast carrier relaxation in graphene has been studied vigorously, transport properties of photoexcited carriers in graphene are largely unknown. In this work, we utilize an ultrafast grating imaging technique to measure lifetime (τ r), diffusion coefficient (D), diffusion length (L) and mobility (µ) of photoexcited carriers in monoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…For our photodetector based on p-n heterojunction, there are three main reasons for the fast response speed: (1) The vertical heterojunction structure has intrinsically short transport length for carriers [45]. (2) The strong build-in electric field from the DSM and PbPc thin film can greatly facilitate the separation and collection of the photocarriers, inducing the high response speed [46,47]. (3) Moreover, when the heterojunction is applied with reverse bias voltage, the electric field caused by reverse bias is consistent with the build-in electric field, so the barrier height is enhanced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For our photodetector based on p-n heterojunction, there are three main reasons for the fast response speed: (1) The vertical heterojunction structure has intrinsically short transport length for carriers [45]. (2) The strong build-in electric field from the DSM and PbPc thin film can greatly facilitate the separation and collection of the photocarriers, inducing the high response speed [46,47]. (3) Moreover, when the heterojunction is applied with reverse bias voltage, the electric field caused by reverse bias is consistent with the build-in electric field, so the barrier height is enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Since the successful preparation of graphene in 2004 [1], graphene has been widely studied due to its excellent carrier transport performance, unique two-dimensional (2D) energy dispersion, and stable electrical and optical properties [2][3][4]. At present, graphene has shown extremely high application value in many fields such as photoelectric detection, solar cell and optical modulator [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…It was experimentally shown that the carrier lifetime only decreases slightly with carrier density in graphene [ 7 ]. Taking into account this approximation and the known value of the carrier mobility at the Dirac point (determined from Van der Pauw measurements), the data presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The application of two-dimensional (2D) materials in electronic devices [ 1 6 ] requires the development of appropriate measurement methods for determining their typical semiconductor parameters, i.e., carrier mobility (μ) and lifetime (τ). Among these methods, contactless techniques [ 7 8 ] and mobility extraction methods based on field-effect measurements [ 9 ] are of great importance. Here we show a contactless method for determining these parameters in 2D semiconductors that is based on the photomagnetoelectric (PME) effect [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experimental setup of NGI is very simple because we monitor the temperatureinduced probe reflectivity change instead of diffraction. Recently, we implemented the same grating imaging technique into our femtosecond pump-probe spectrometer to detect carrier diffusion in graphene [31] and GaAs/AlAs SLs [32]. Our new technique is developed based on ns-TDTR due to its several advantages compared with an fs-TDTR.…”
Section: Introductionmentioning
confidence: 99%